Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Muatan IPA Dengan Menggunakan Model Nakama Kelas V - Muhammad Arsyad Jalalludin; Novitawati (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem addressed in this research is the low level of students' critical thinking skills. This is caused by the lack of student engagement in learning, difficulty in working on group assignments, inadequate understanding of subject concepts, and reliance on rote memorization. The effort to address these issues is by implementing the NAKAMA learning model in the classroom. The aim of this research is to describe the improvement in the quality of students' critical thinking skills. This study employs a qualitative and quantitative approach through classroom action research (CAR). The research subjects consist of 20 fifth-grade students from SDN Sungai Gampa Asahi. The results of this study indicate an improvement in students' critical thinking skills in the first meeting by 40% with a criteria of being fairly skilled, in the second meeting by 50% with a criteria of being fairly skilled, in the third meeting by 70% with a criteria of being skilled, and in the fourth meeting by 80% with a criteria of being highly skilled, thus meeting the expected standards according to the success indicators.